2014
DOI: 10.1039/c3cc49633c
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed ortho-C–H amination of protected anilines with secondary amines

Abstract: A practical Cu-catalyzed picolinamide-directed o-amination of anilines showing excellent mono-substitution selectivity and high functional group tolerance has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 56 publications
0
44
0
1
Order By: Relevance
“…[19] The oxidants were finally screened by using [Cp*RhCl 2 ] 2 as ap recatalyst and DMF as as olvent. Cu(OAc) 2 provedt ob et he best oxidanta mong the tested oxidants (Cu(OAc) 2 ,C u(OTf) 2 , Ag 2 CO 3 ,a nd AgOAc;e ntry 8v s. entries [9][10][11]. The yield of benzannulation product 5aa wasf ound to increasew ith increased [Cp*RhCl 2 ] 2 loading (entry 12, 81 %).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[19] The oxidants were finally screened by using [Cp*RhCl 2 ] 2 as ap recatalyst and DMF as as olvent. Cu(OAc) 2 provedt ob et he best oxidanta mong the tested oxidants (Cu(OAc) 2 ,C u(OTf) 2 , Ag 2 CO 3 ,a nd AgOAc;e ntry 8v s. entries [9][10][11]. The yield of benzannulation product 5aa wasf ound to increasew ith increased [Cp*RhCl 2 ] 2 loading (entry 12, 81 %).…”
Section: Resultsmentioning
confidence: 98%
“…Among the directing groups employed, acylaminog roups are frequently utilized because they can be easily installed into the substrates and convertedt o other functional groups. [5] For example, the acylamino groups linked on aromatic rings were successfully used as the directing groups for new carbon-carbon( including C aryl -C alkenyl , [6] C aryl -C aryl , [7] C aryl -C alkyl , [8] and C aryl -C carbonyl [9] )a nd carbon-heteroatom (including C aryl -N, [10] C aryl -O, [11] C aryl -B, [12] C aryl -Cl, [13] C aryl -Br, [14] and C aryl -I [15] )bond formation as well as for the carbocycle and heterocycle construction. [16][17][18] It was demonstrated that highly functionalized indoles can be efficiently synthesized throughd irect CÀHb ond functionalization in the presence of ac ationic rhodium(III) catalystb yu sing an acetylamino group as the directing group [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…By using a picoline-type director, anilides can also couple with alkylamines in a dehydrogenative manner to form the corresponding 1,2-diaminobenzene derivatives (Eqs. 33 and 34) [59,60]. The hypervalent I(III) reagent, PhI(OAc) 2 is a critical oxidant, and the reaction occurs under relatively mild conditions (rt-80 C).…”
Section: %mentioning
confidence: 99%
“…Following the success of Daugulis’ work, Rodríguez, Arrayás et al . and Chen's group independently reported the picolinamide (PA)‐assisted copper‐catalyzed amination of anilines with cyclic secondary alkylamines (Scheme ).…”
Section: Transition‐metal‐catalyzed Direct C−h Amidation and Aminatimentioning
confidence: 99%